Gα12-Mediated Pathway Promotes Invasiveness of Nasopharyngeal Carcinoma by Modulating Actin Cytoskeleton Reorganization - Liu, Shu-Chen; Jen, Yee-Min; Jiang, Shih Sheng; Chang, Junn-Liang; Hsiung, Chao A.; Wang, Chih-Hung; Juang, Jyh-Lyh (Cancer research (Chicago, Ill.), 2009)
The molecular mechanisms behind the aggressiveness of nasopharyngeal carcinoma (NPC), a highly invasive and metastatic head and neck malignancy, have not been made clear. In this study investigating these mechanisms, guanine nucleotide-binding protein α12 subunit (Gα12) signaling was found by microarray analysis to be increased in primary NPC cells and NPC-derived cell lines. Using small interfering RNA to knock down Gα12 in NPC cells resulted in a reduction in cell migration and invasion as well as a reversal in fibroblastoid morphology. Using microarray analysis, we also found a reduction in expression of key actin dynamics regulators and several epithelial-to-mesenchymal transition–related genes in Gα12-depleted NPC cells. Knocking down one of those genes, IQ motif containing GTPase activating protein 1, reduced the migration and formation of adherens junctions and reversed the fibroblastoid morphology of NPC cells, as knocking down Gα12 was found to do. Immunohistochemical analysis found NPC tumors to have significantly greater levels of Gα12 protein than the normal basal epithelial cells. Quantitative real-time PCR analysis revealed a significant correlation between Gα12 mRNA levels and NPC lymph node metastasis. Together, our findings support a model in which activation of Gα12 signaling promotes tumorigenesis and progression of NPC by modulating actin cytoskeleton reorganization and expression of epithelial-to-mesenchymal transition–related genes. [Cancer Res 2009;69(15):6122–30]